REQUIREMENTS OF FOREIGN LANGUAGE TEACHING METHODOLOGY PROGRAMS AND CEFR-BASED LANGUAGE STANDARDS IN UZBEKISTAN (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2025)
In recent decades, foreign language education has become a key component of national development strategies worldwide. Uzbekistan has placed special emphasis on improving the quality of foreign language teaching by reforming teacher education programs and adopting internationally recognized language standards. This article provides a comprehensive analysis of the requirements of foreign language teaching methodology programs and examines the role of the Common European Framework of Reference for Languages (CEFR) as the foundation of foreign language standards in Uzbekistan